Factors affecting outcome of decompressive hemicraniectomy in malignant middle cerebral artery infarction - Koirala, Sagar; Bhandari, Shreeram; Lohani, Subash (Nepal Journal of Neuroscience, 2021)
Introduction: Decompressive Hemicraniectomy (DHC) is a standard surgical management of malignant MCA (MMCA) infarction. This study was conducted to review the outcome of surgery and to find out factors associated with favorable outcomes at a tertiary level neurosurgery referral centre. Methods and Materials: This is a retrospective study conducted over a period of three years from 2017 to 2019. Patient charts were reviewed for variable like age, sex, timing of surgery, GCS at presentation, length of ventilation, length of ICU admission and length of hospital stay. Primary outcome measure was GOSE: favorable (<=4) and unfavorable (>=5). SPSS version 23 was used for analysis. Results: A total of 28 patients underwent DHC out of which 21 patients were available for analysis. Mean age of patients was 58.62 years. Mean GCS on arrival was 11.86. Mean interval duration between event and surgery was 51.88 hours. Mean duration of ventilation was 4.43 days. Mean length of ICU stay was 5.95 days. Mean hospital stay was 22.33 days. Mean GOSE was 2. Mean age was significantly lower in patients with favorable GOSE. Early surgery had better mean GOSE which was not significant statistically. Conclusion: Patients with age less than 50 years have favorable GOSE despite MMCA infarction if decompressive hemicraniectomy is performed to accommodate brain swelling. Early surgery at presentation rather than waiting for deterioration might improve the outcome.